HO-1 protects smokers exposed to artificial stone dust for pulmonary function tests deterioration - Ophir, Noa; Bar-Shai, Amir Bar-Shai; Kramer, Mordechai R; Grubstein, Ahuva; Israeli-Shani, Lilach; Fireman, Elizabeth (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: The Heme Oxygenase system, along with its catabolism products, is involved in a variety of crucial physiological functions, including cytoprotection, inflammation, anti-oxidative effects, apoptosis, angiogenesis, and vascular regulation. Objectives: To analyze the Heme Oxygenase -1 (HO-1) mediated effect of mild deterioration of pulmonary function testing (PFT) in exposed artificial stone smoking workers. Methods: One hundred stone workers divided into current smokers, ex-smokers and never smokers underwent Low Resolution Computed Tomography, PFT, induced sputum (IS) Particle Size Distribution (PSD) and Real Time PCR in IS samples. Results: Smoking status had no significant effect on PFT results but it altered the IS differential cell counts. There was significantly less decline in PFT over time for the smokers group. There was a significantly lower fraction of small particles (